2021
DOI: 10.1590/1678-4499.20200494
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with nitric oxide preserves the quality of cold stored ‘Cripps Pink’ apples

Abstract: The objective of this work was to evaluate the effect of pre-storage fruit treatment with nitric oxide (NO) on the quality maintenance of cold stored 'Cripps Pink' apples. The following treatments were evaluated: 0 µL•L -1 of NO (control); 10 µL•L -1 of NO for 2 h; 10 µL•L -1 of NO for 4 h; 10 µL•L -1 of NO for 8 h; and 20 µL•L -1 of NO for 2 h. Fruit treated with NO, regardless of concentration and application time, had a greener skin background color than the control, especially those treated with 10 µL•L -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…It is possible to attribute the effect of 1‐MCP on the lower respiratory activity of 1‐MCP‐treated fruit. In the present study, there is no positive effect of NO on the maintenance of TA, as well as observed in “Galaxy” (Brackmann et al., 2017) and “Cripps Pink” apples (Steffens et al., 2021).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…It is possible to attribute the effect of 1‐MCP on the lower respiratory activity of 1‐MCP‐treated fruit. In the present study, there is no positive effect of NO on the maintenance of TA, as well as observed in “Galaxy” (Brackmann et al., 2017) and “Cripps Pink” apples (Steffens et al., 2021).…”
Section: Resultssupporting
confidence: 70%
“…NO treatment of “Cripps Pink” apples had no effect on flesh firmness (Table 1). There was also no effect of NO on the maintenance of flesh firmness in “Galaxy” apples after CA storage (Brackmann et al., 2017) and “Cripps Pink” apples cold stored (Steffens et al., 2021). The effect of NO on ripening‐related events, such as a reduction in flesh firmness, has been attributed to the reduction of ethylene synthesis in treated fruits (Palma et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The application of only one dose of NO at the beginning of storage was not efficient in delaying ethylene production and reducing respiration (Table 1), unlike that observed in “Galaxy” (Brackmann et al, 2017) and “Cripps Pink” apples (Steffens, Miqueloto, et al, 2021). According to Manjunatha et al (2010), the effect of NO is dependent on the fruit species, which may explain the difference observed between the results obtained with banana and apple.…”
Section: Resultsmentioning
confidence: 85%
“…The reduction in ethylene production also occurs due to the interaction of NO with other plant signaling/phytoregulatory molecules (such as salicylic acid), modulating and inhibiting the expression of genes involved in ethylene biosynthesis (Hong et al, 2014). The application of NO in other climacteric fruit, such as plum (Steffens et al, 2022), apple (Steffens, Miqueloto, et al, 2021), and tomato (Zuccarelli et al, 2020), also reduced ethylene production.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
See 1 more Smart Citation